Namaszczenie Jezusa w Betanii (Mt 26,6–13) - Florczyk, Łukasz (Poznańskie Studia Teologiczne, 2020)
The action of pericope that describes the anointing of Jesus (Matt. 26:6–13) took place in Bethany, in Judea. These areas were then part of the Great Roman Empire. Christ foretold that the woman who poured out the precious oil on His head in the house of Simon the Leper would know the whole world. That is what exactly happened. Many Christians do not know much about history of the Ro- man Empire, but probably everyone has heard of a nameless woman who anointed Jesus shortly before His passion and death. The woman embarrassed the apostles, her generous gesture toward Christ contrasted with the conspiracy of the chief priests and the elders of the people (Matt. 26:3–5) and the betrayal of Judas (Matt. 26:14–16).